Deployment of IoT based smart environment : key issues and challenges - Sehrawat, Deepti; Gill, Nasib Singh (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) is viewed as a dynamic technological revolution representing future communications and computing in several areas. It introduces physical objects in the sphere of cyber world. IoT is not about a single technology but various complementary technological developments which provides ways to bridge the gap between the real world and the virtual world. A number of wireless sensor technologies are implemented in IoT viz. RFID, ZigBee, actuators, WiFi and wireless sensor networks (WSNs). This paper presents various key technologies involved in IoT and its detailed architecture. IoT architecture explains function of each layer with respect to the technologies and the devices that surround each layer. Each layer has its specific security issues. This paper presents various security threats related to each IoT layer and the specific security requirements. Information security, data protection, and user's privacy are among important key areas in IoT. This paper in the nutshell presents new challenges posed by IoT so that further work can be undertaken in creating a robust, efficient and smart environment for IoT based applications.